(untitled) (Research, Society and Development, 2021)
Basically, the state has the authority to regulate the use of land rights in the territory of Indonesia. However, the problem that often occurs is the disagreement between the Land Acquisition Committee and the holders of land rights in determining the amount of compensation, resulting in problems such as what happened in Palu after the earthquake which flattened housing buildings and required a plot of land for housing construction. Therefore, the aim of this research is to explore legal efforts for land rights that are affected by the acquisition for the construction of permanent housing to meet housing needs after the earthquake in Palu. The research method that used is legal research, while the approach that used in this research is statute approach. The results of data analysis shows the legal action of land rights holders that are affected by land acquisition for the construction of permanent housing by means of certificate cancellation, the cancellation of the certificate is based on law. Land acquisition for the public interest, including the interests of the nation and the State as well as the common interest of the people, can revoke land rights by giving compensation.